The effectiveness of foreign aid to education: What can be learned? - Abby Riddell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper reviews what has been learned over many decades of foreign aid to education. It discusses what works and what does not and in this discussion draws attention to the fact that even a simple assessment requires more than providing a uniform check-list of inputs. It shows the positive contribution that aid has made to education in aid-recipient countries, the most tangible outcome of which is the contribution that aid makes to expanding enrolments especially of basic education. But the paper also indicates that there is a considerable gap between what aid does and what it could potentially achieve, especially in relation to its contribution to improvements in educational quality. Perhaps the paper's most important conclusion relates to the contribution of aid to capacity development in education - on the one hand an issue of central importance, but on the other, one in which the record has been one of systemic weaknesses and failures and in which few lessons seem to have been learned. This review shows that many of the lessons of what works in foreign aid to education are known, but they are not implemented. These lessons are of two sorts, the first cluster relates to the interface of aid with education systems in recipient countries. To make a difference, what is of paramount importance is to start at the level of the whole education sector - rather than to pick out the sub-sector most popular with donors and channel a disproportionate share of funds to make this 'work' better, for this distorts a government's sector-wide planning. The second cluster of lessons are those related to the 'nuts and bolts' of education systems themselves - what makes them work, how the different bits fit together and how aid monies can distort priorities, making the government's co-ordination efforts difficult as well as creating fragmented accountability. This review demonstrates the distortions caused by focusing on enrolments and insufficiently on quality, on products such as plans and educational management information systems (EMIS), and 'inputs' rather than processes and outcomes, what goes on in the classroom, what the students learn, whether the teachers' pay and status are sufficient to keep them in the classroom and continuing to teach. Sustainable education outcomes will not be achieved merely by reproducing yet more successful, but individual projects. Perversely, development agencies which focus only on demonstrable short-term impact may well be contributing, unwittingly, to an undermining of long-term impact on the education systems and their deepening development, to whose progress they are trying to contribute.
Keywords: F35; I22; I25; I28; I38; 330; education; foreign aid; developing countries; policy effectiveness; Entwicklungshilfe; Wirkungsanalyse; Bildung; Entwicklungsländer